Disminución de la agudeza visual asociada con la retinopatía hipertensiva en paciente de 70 años. - Carcelén Cedeño, Anahi Dayanara (2021)
It is known that arterial hypertension constitutes a serious health problem, causing significant morbidity in the adult population worldwide and produces organic vascular lesions in what are known as white organs (heart, kidney, brain, retina). As a professional in the field of optometry on a daily basis, it is essential to perform the function of a professional in primary care in Visual Health. Most of the patients who come to our optometric consultations present ocular conditions that require greater management techniques. In a large percentage these conditions are manifest, but in many cases, it is necessary to continue with the updating protocol rigorously that reveals the identity of these pathologies. The case that concerns me is that of a patient who comes to the consultation referring to a general picture of decreased vision along with a characteristic headache; there is knowledge about her underlying disease but the patient does not understand the consequences that this brings to her vision. In conclusion, the presence of hypertensive retinopathy is related to the longest evolution time of the disease.